Actividades de educación emocional para mejorar las habilidades sociales en alumnos de tercer año de básica en el barrio Tunantza - Zamora, periodo 2020. - Romero Salinas, Anthonny Daniel (2021)
In children learning social skills are important since they allow to develop from an early age communication skills, learn social norms, affective expressions and conflict resolution, otherwise children who have difficulties with the aforementioned element tend to present personal problems and in their personal environment in the short and long term, which is why in this thesis entitled: Emotional education activities to improve social skills in third grade students in the Tunantza - Zamora neighborhood, period 2020, the objective was to design emotional education activities to improve social skills in students, a non-experimental design was applied in which ten third grade students participated, the Goldstein (1978) social skills checklist scale was used as an instrument. The most important results for the researcher in relation to the social skills of the investigated population are that in low level (30%) and deficient (20%) are in the basic social skills, in the same way the advanced social skills in low level are 40%, in relation to the skills related to feelings with the same percentage of 20% are in medium and deficient level, finally in the alternative skills to aggression are in low level 20% and in deficient level 10% of the investigated students. Concluding that the investigated population demonstrates low and deficient levels in social skills, in view of this reality, a proposal based on emotional education activities is presented as an alternative to improve social skills.